Hydrative trimerization of acetylene into 2-vinyloxy-1, 3-butadiene in the KOH/DMSO system: a quantum chemical insight. Issue 9 (25th February 2015) - Vitkovskaya, Nadezhda M.; Larionova, Elena Yu.; Skitnevskaya, Anna D.; Trofimov, Boris A.
Graphical abstract: Abstract: The previously described one-pot hydrative trimerization of acetylene to give 2-vinyloxy-1, 3-butadiene in the KOH/DMSO superbase system has been studied using the MP2/6-311++G ∗∗ //B3LYP/6-31+G ∗ quantum chemical framework in which the superbase system was modeled by n DMSO·KOH complexes ( n  = 1 or 5). According to the results obtained, initial formation of acetaldehyde and its ethynylation to give acetylenic alcohol occurs in the coordination sphere of the K + cation. The rate-determining step is the addition of the hydroxide ion to the acetylene molecule.